University-Industry collaboration in research and development in Malaysian Universities - Othman, Norazimah (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2016)
The focus of this study is on types of university-industry collaboration in R&D projects in Malaysian universities. The study identified the benefits derived from University-Industry collaborations as it relates to performance of R&D project and the characteristics of R&D projects that encourage industry to collaborate with universities. It also makes recommendations towards increasing performance of R&D projects based on the data collected and analysed. Exploratory approach was used in this study. This approach explored the collaboration types and how it contributed to R&D performance. Quantitative analysis was used by analysing questionnaire data. The reliability of the questionnaire items was tested. The respondents were people with experience in U-I collaborations. Data was analysed based on the five major elements in the theoretical framework. These are: benefits, performance, characters, practice and barrier. Based on the findings from the study, all of these five elements should be combined to ensure better R&D performance. The contribution of this study is the suggestions to universities in Malaysia and the Ministry of Higher Education (MOHE) to encourage increasing numbers of U-I collaborations.